2021
DOI: 10.3389/fpsyg.2021.700742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity and Mindfulness on Resilience and Depression During the First Wave of COVID-19 Pandemic

Abstract: The first wave of the COVID-19 pandemic generated a significant number of stressors that the Swiss population had to deal with. In order to cope with and adapt to such adversity, it is essential to have protective factors that allow for resilience. The objective of this study was to investigate the effects of mindfulness and physical activity on depression and resilience during the first wave of the COVID-19 pandemic. A quantitative method was adopted asking participants who were engaged in physical activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Adequate implementation of techniques that eliminate the high level of the cognitive component of the variable can, according to our assumptions, help athletes increase their performance in a given type of sport [ [1] , [2] , [3] , [4] , [5] , 88 ]. This is also in line with research dealing with increasing psychological readiness using yoga exercises [ 66 ], meditations [ [67] , [68] , [69] , [70] ], or using Schultz's autogenic training or Jacobson's progressive relaxation [ [71] , [72] , [73] , [74] , [75] ].…”
Section: Discussionsupporting
confidence: 84%
“…Adequate implementation of techniques that eliminate the high level of the cognitive component of the variable can, according to our assumptions, help athletes increase their performance in a given type of sport [ [1] , [2] , [3] , [4] , [5] , 88 ]. This is also in line with research dealing with increasing psychological readiness using yoga exercises [ 66 ], meditations [ [67] , [68] , [69] , [70] ], or using Schultz's autogenic training or Jacobson's progressive relaxation [ [71] , [72] , [73] , [74] , [75] ].…”
Section: Discussionsupporting
confidence: 84%
“…In a study of college students during the pandemic, an online, group-based mindfulness intervention was found to improve three out of six aspects of psychological well-being, namely, self-acceptance, autonomy, and environmental mastery [ 46 ]. Interestingly, a survey-based study in Switzerland found that while mindfulness improved initial resilience, physical activity helped to maintain resilience over time [ 47 ]. The latter findings underscore the integration of mental and physical health and the ability of physical health to support mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of mindfulness could also have been useful during this time, as the experience of focusing on and appreciating the present in a time of great uncertainty about the future may have been helpful for people (Brose et al, 2021). These findings can further support the idea that mindfulness meditation, as well as other strategies and techniques that promote mindfulness (Pagnini et al, 2016), is a tool for coping with adversity during a potentially traumatic event (Antonini Philippe et al, 2021). The studies included in the present review have some limitations.…”
Section: Meta Analysismentioning
confidence: 95%